Risk assessment of N-nitrosodiethylamine (NDEA) and N-nitrosodiethanolamine (NDELA) in cosmetics. Issue 12 (18th June 2018) - Lim, Duck Soo; Roh, Tae Hyun; Kim, Min Kook; Kwon, Yong Chan; Choi, Seul Min; Kwack, Seung Jun; Kim, Kyu Bong; Yoon, Sungpil; Kim, Hyung Sik; Lee, Byung-Mu
ABSTRACT: N -nitrosamines and their precursors found in cosmetics may be carcinogenic in humans. Thus the aim of this study was to carry out risk assessment for N -nitrosamines ( N -nitrosodiethanolamine [NDELA], N -nitrosodiethylamine [NDEA]) and amines (triethanolamine [TEA], diethanolamine [DEA]) levels in cosmetics determined using validated liquid chromatography–tandem mass spectrometry (LC–MS/MS) procedures. NDELA and NDEA concentrations were present at levels of "not detected" (N.D.) to 596.5 μg/kg and N.D. to 40.9 μg/kg, respectively. TEA and DEA concentrations ranged from N.D. to 860 μg/kg and N.D. to 26.22 μg/kg, respectively. The nitrite concentration (3–2250 mg/l), number of nitrosating agents to a maximum 5, and pH (3.93–10.09) were also assessed. The impact of N -nitrosamine formation on the levels of TEA, DEA, nitrite, and other nitrosating agents was also examined. N -nitrosamine concentrations correlated with the number of nitrosating agents and nitrite concentrations. Data demonstrated that higher nitrite concentrations and a greater number of nitrosating agents increased NDELA and NDEA yields. Further, the presence of TEA and DEA exerted a significant influence on N -nitrosamine formation. Risk assessments, including the margin of exposure (MOE) and lifetime cancer risk (LCR) for N -nitrosamines and margin of safety (MOS) for amines, were calculated using product type, use pattern, and concentrations. Exposure to maximum amounts of NDELA and NDEA resulted in MOE > 10, 000 (based upon the benchmark dose lower confidence limit 10%) and LCR <1 × 10 −5, respectively. In addition, TEA and DEA concentrations in cosmetic samples resulted in MOS values >100. Therefore, no apparent safety concerns were associated with cosmetic products containing NDELA, NDEA, TEA, and DEA in this study. However, since amines and nitrosating agents produce carcinogenic nitrosamines, their use in cosmetics needs to be minimized to levels as low as technically feasible.